I frammenti degli Agathoi di Ferecrate, o dei limiti della ricostruzione - Napolitano, Michele (Lexis, 2021)
Although only four fragments of Pherecrates’ Agathoi survive, it is still possible, albeit with caution, to imagine that the play was aimed at degenerate aristocrats, to whom the title of the play would refer. To try to prove this, I propose a new, detailed exegesis of three of the four surviving fragments of the play.